Monofilamentary Ag/Bi : 2212 tapes - Effects of silver powder addition - Santos, Dayse Iara dos [UNESP]; Rodrigues, D.; Rubo, EAA; Cursino, E.; Salgado, L.; Filho, F. A. (Trans Tech Publications Ltd, 2005)
The Bi-Sr-Ca-Cu-O system has been one of the most studied superconducting ceramic materials for industry applications. The most of the studies with this aim are on silver/ceramic composites, due to the benefits and great compatibility of this metal with the oxide. Tapes made by the powder in tube (PIT) method have been successfully tested in pilot power plants in many countries but in Brazil. In this paper, 5, 10, and 20-wt% silver powders are introduced to compose the core of the tape along with the Bi:2212 ceramic powder. The results of electrical experiments are compared with those made with no silver addition Ag tapes. The best current density, at 60 K and no applied magnetic field, was found for the 10-wt% silver proportion, doubling the value obtained for the tape with no silver in the core.
Keywords: Ag/BSCCO monofilamentary tapes; PIT tapes; silver addition